Two-phase flow in metal monoliths: hydrodynamics and liquid-liquid extraction - Deshpande, Jaydeep B.; Gosavi, Abha; Kulkarni, Amol A. (Canadian Journal of Chemical Engineering, 2014)
This work aims to explore the application of metal monoliths as a scale-up option for efficient liquid-liquid extraction. The pressure drop, mass transfer and residence time distribution are measured for low Ca (approximate to 10(-5)) with monoliths having three different cell densities. The cross-over section between two monoliths was seen to enhance mixing in the column. However, the RTD of two-phase liquid-liquid up-flow was inferior to the single phase RTD. For higher cell density substrates, the cross-over zones seem to cause trapping of slugs due to non-superimposing channel ends. Relatively high shear rates through the film of continuous phase helped enhance the mass transfer rates, thereby helping to achieve the desired extraction in a short column. The entrance sections and cross-over zones between the monoliths adversely affected the extraction for higher cell density monoliths. The analysis of data supports use of low cell density monolith for better performance and scale up.
Keywords: capillary; hydrodynamics; liquid-liquid extraction; monolith; slug flow

Effect of interfacial mass transfer on the dispersion in segmented flow in straight capillaries - Deshpande, Jaydeep B.; Kulkarni, Amol A. (AICHE Journal, 2015)
The effect of interfacial mass transfer on the extent of dispersion in liquid-liquid segmented flow in straight capillaries is studied. In the absence of interfacial mass transfer, dispersion coefficient was seen to go through a minimum with increasing flow rates. In the presence of mass transfer, physicochemical properties of both the phases and slug lengths were seen to vary along the capillary length. The extent of dispersion was always higher in the presence of interfacial mass transfer. The predictions using axial dispersion model deviated noticeably for larger capillaries as the model does not account for varying buoyancy, dynamic contacting, and Marangoni convection. Simulations of a first-order interfacial reaction considering varying slug lengths showed a significant change in optimum operating parameters than the conventional approach. A special case of drop-on-demand type of controlled two-phase flow in capillaries was also studied. (c) 2015 American Institute of Chemical Engineers.
Keywords: capillary; dispersion; interfacial mass transfer; segmented flow; slugs

Continuous interfacial centrifugal separation and recovery of silver nanoparticles - Deshpande, Jaydeep B.; Navale, Govinda R.; Dharne, Mahesh S.; Kulkarni, Amol A. (Chemical Engineering & Technology, 2020)
Continuous-flow separation and recovery of silver nanoparticles (AgNPs) using an annular centrifugal extractor (ACE) is demonstrated. Separation was achieved at the liquid-liquid interface based on the balance between centrifugal force and the solubility of the capping agent. A mathematical model is presented to understand the mechanism in greater detail. The separation of poly(vinylpyrrolidone) (PVP)-coated AgNPs in an ACE using a strong immiscible solvent was performed. The material accumulated at the interface was separated periodically without discontinuing the operation. The method is also suitable for separation of large particles or 1D/2D nanostructures even employing a single annular centrifugal extractor. Stable AgNPs were selected for a detailed antimicrobial activity study.
Keywords: Annular centrifugal extractor; Antimicrobial activity; Continuous-flow separation; Liquid-liquid interface; silver nanoparticles

Quantitative understanding of nucleation and growth kinetics of silver nanowires - Patil, Suneha; Kate, Prachi R.; Deshpande, Jaydeep B.; Kulkarni, Amol A. (Chemical Engineering Journal, 2021)
We have demonstrated that using polyol synthesis, it is possible to prepare high aspect ratio silver nanowires by controlling the experiments for process related issues which are usually ignored, viz. the overhead space in the batch reactor. It is found that by controlling the presence/absence of NOx gases with refluxing of nitric acid in the batch reactor with an overhead space of 80% volume, near complete conversion (-99%) of high aspect ratio NWs (-1000) can be attained. We provide a detailed understanding of other factors assisting in rapid polyol synthesis like temperature, stirring rate, Chloride ion concentration, optimal PVP weight ratios and PVP/AgNO3 ratio that can lead to high aspect ratio NWs. Besides the process parameters and reagent concentration effects, kinetic studies based on our nucleation and R-C Model evaluate the overall reaction rate constants for silver nanowires and the JMAK approach is used to theoretically validate our experimental results of the reactor headspace having strongest effect on the aspect ratios. Our study highlights the importance of various complications in the polyol synthesis, through detailed kinetic modelling and affixes values of temperature, reactor headspace, stirring rate and residence time in order to achieve reproducible synthesis of nanowires with complete conversion along with a method to separate these nanowires.
Keywords: Conducting inks; growth; Nucleation; Reaction kinetics; Redox-crystallization; Silver Nanowires